Perbandingan Histopatologis Vaskularisasi, Adneksa Kulit dan Sel Jaringan Ikat Parut Akne dengan Terapi Kombinasi Microneedling dan Subsisi antara yang Disertai Platelet Rich Plasma dengan Disertai Larutan Salin Fisiologis - Rini A.C. Saragih (Majalah Kedokteran Nusantara The Journal Of Medical School, 2018)
Introduction: Multimodal approach for acne scar is usually needed to get satisfying result. Medicalmicroneedling technique has been shown to enhance skin remolding that increase new tissue formation.Platelet rich plasma (PRP) was reported promoting more organized collagen compared to tissue fromwounds that were not treated with PRP.Methods: This research is a non-randomized double blind clinical trial, aimed to investigate the effect ofmicroneedling and subcision combination therapy followed by platelet rich plasma application inhistopathology of vascularization, skin adnexa, and connective tissue cells on acne scar. Punch biopsywas performed on a rolling acne scar before first treatment and on rolling acne scar of each cheek, 4weeks after second treatment.Results: After microneedling and subcision combination therapy followed by platelet rich plasmaapplication, vascularization was found in 66.7% specimens and more skin adnexa was found in 83.3%specimens.Discussion: Histopathology of specimens after microneedling and subcision combination therapyfollowed by platelet rich plasma application compared to specimens after microneedling and subcisioncombination therapy followed by normal saline application showed statistically significant difference invascularization, but no statistically significant difference in skin adnexa and connective tissue cells.Key words: acne scar, microneedling, subcision, PRP.ABSTRAKPendahuluan: Pendekatan multimodal untuk parut akne umumnya diperlukan untuk mendapatkan hasilyang memuaskan. Teknik medical microneedling telah terbukti meningkatkan remolding kulit sehinggameningkatkan pembentukan jaringan baru. Platelet rich plasma (PRP) dilaporkan menimbulkan kolagenyang lebih tersusun dibandingkan jaringan dari luka yang tidak diberikan PRP.Metode: Penelitian ini merupakan suatu non-randomized double blind clinical trial yang bertujuan untukmengetahui pengaruh kombinasi teknik microneedling dan subsisi disertai pemberian PRP terhadapgambaran histopatologi vaskularisasi, adneksa kulit, dan sel jaringan ikat pada parut akne. Biopsi plongdilakukan pada salah satu parut akne tipe rolling sebelum terapi pertama, dan pada salah satu parutakne tipe rolling pada masing-masing pipi, 4 minggu setelah terapi kedua.Hasil Pada spesimen setelah terapi kombinasi microneedling dan subsisi disertai pemberian PRP,vaskularisasi dijumpai pada 66.7% spesimen dan pertambahan adneksa kulit dijumpai pada 83.3%spesimen.Simpulan Perbandingan gambaran histopatologi spesimen setelah terapi kombinasi microneedling dansubsisi disertai pemberian PRP dengan yang disertai pemberian NaCl 0,9% menunjukkan perbedaaanbermakna secara statistik pada vaskularisasi, namun tidak dijumpai perbedaan bermakna secarastatistik pada adneksa kulit dan sel jaringan ikat.Kata kunci: parut akne, microneedling, subsisi, PRP